2016
DOI: 10.1177/1071100716649926
|View full text |Cite
|
Sign up to set email alerts
|

Supramalleolar Osteotomy With or Without Fibular Osteotomy for Varus Ankle Arthritis

Abstract: Level III, retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
57
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 43 publications
2
57
0
4
Order By: Relevance
“…There are numerous reports on supramalleolar osteotomy with or without fibular osteotomy for varus ankle arthritis. Hongmou et al [25] reported that fibular osteotomy may be necessary in supramalleolar osteotomy cases with a large talar tilt and small tibiocrural angles. Stufkens et al [26] also reported that only supramalleolar osteotomy with fibular osteotomy shifts the pressure laterally for varus ankle arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous reports on supramalleolar osteotomy with or without fibular osteotomy for varus ankle arthritis. Hongmou et al [25] reported that fibular osteotomy may be necessary in supramalleolar osteotomy cases with a large talar tilt and small tibiocrural angles. Stufkens et al [26] also reported that only supramalleolar osteotomy with fibular osteotomy shifts the pressure laterally for varus ankle arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, allografts are often not commercially available in some countries owing to the high costs, lack of approval for use, or religious reasons (29). Therefore, alternative graft substances, such as coralline hydroxyapatite (18), interconnected porous calcium hydroxyapatite ceramic (23,24), and TCP (10,22,24), have been developed and used in various foot and ankle surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…However, in 2006, van der Krans et al (10) observed nonunion after using a tricalcium phosphate (TCP) block in an adult male weighing 110 kg. Although bone graft substitutes have been successfully used in around-the-knee osteotomies (19)(20)(21), few foot and ankle surgeons recognized their value as block bone grafts until the mid-2010s because of the graft's structural fragility (10,18,22).…”
mentioning
confidence: 99%
“…Supramalleolar osteotomy (SMOT) is an effective procedure for the treatment of midstage asymmetric ankle osteoarthritis [1][2][3][4]. Related studies have proved that the key factors affecting the postoperative curative effect of SMOT are the postoperative ankle Takakura stage [5], lower limb power line [6] and ankle angles [7]; but SMOT uses conventional operation (CO) method often does not perfectly accomplish these surgical aims leading to some patients have unsatisfactory outcomes [8,9]. The reasons include preoperative planning dependence on freehand drawing, and surgeons determine the operative procedure all depend on the surgeon's experiences and fluoroscopies [10].…”
Section: Introductionmentioning
confidence: 99%